2014
DOI: 10.1039/c4sm00632a
|View full text |Cite
|
Sign up to set email alerts
|

Does dynamic vulcanization induce phase separation?

Abstract: Immiscible and miscible blends of poly(vinylidene fluoride) (PVDF) and acrylic rubber (ACM) were subjected to dynamic vulcanization to investigate the effect of crosslinking on phase separation. As a result of different processability, mixing torque behavior of miscible and immiscible blends was significantly different from one another. Scanning electron microscopy (SEM) was used to investigate the morphology of the system. After dynamic vulcanization, submicron ACM droplets were observed in the samples near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Figure 10(A), (B) and (C) represent the magnified view of the domain morphology of P33, P34 and P35 TPV systems respectively and the distribution of particle size M a n u s c r i p t 22 | P a g e for the respective TPVs is given in Figure 11. From these images it is evident that the dispersed rubber particles are actually the disintegrated rubber agglomerates containing nano-sized rubber particles ranging from 60-100 nm which is quite similar to the observation recently made by Wu et al [40] and Abolhasani et al [41]. For P33 TPV (Figure 10(A)), the rubber nano-particles are heavily shadowed by the S-EB-S phase due to the higher proportion of S-EB-S (60 weight percentage), which makes the rubber network less responsive during the scan resulting in poor quality photo-micrographs.…”
Section: (A) (B) Andsupporting
confidence: 83%
“…Figure 10(A), (B) and (C) represent the magnified view of the domain morphology of P33, P34 and P35 TPV systems respectively and the distribution of particle size M a n u s c r i p t 22 | P a g e for the respective TPVs is given in Figure 11. From these images it is evident that the dispersed rubber particles are actually the disintegrated rubber agglomerates containing nano-sized rubber particles ranging from 60-100 nm which is quite similar to the observation recently made by Wu et al [40] and Abolhasani et al [41]. For P33 TPV (Figure 10(A)), the rubber nano-particles are heavily shadowed by the S-EB-S phase due to the higher proportion of S-EB-S (60 weight percentage), which makes the rubber network less responsive during the scan resulting in poor quality photo-micrographs.…”
Section: (A) (B) Andsupporting
confidence: 83%
“…Recently, we have investigated miscibility of PVDF/ACM (acrylic rubber) blends and the influence of dynamic vulcanization on the processability and morphology of this system. 2,19,20 We demonstrated that PVDF and ACM are miscible in blends with more than 50% ACM. 2 We also showed that crosslinking reactions induced nano-phase separated droplets in blends near the binodal curve, whereas blends in the miscible area were miscible even after dynamic vulcanization.…”
Section: Introductionmentioning
confidence: 75%
“…2 We also showed that crosslinking reactions induced nano-phase separated droplets in blends near the binodal curve, whereas blends in the miscible area were miscible even after dynamic vulcanization. 20 In this study, we want to explore the complicated interrelationship between the crosslinking of amorphous components and crystallization kinetics of crystallizable polymers. It is anticipated that dynamic vulcanization affects the kinetics of crystallization significantly.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The effective way to prepare TPVs is through dynamical vulcanization, [8][9][10] which is the process of cross-linking an elastomer during its melt mixing with a molten plastic under dynamic condition. 11,12 A significant number of TPVs are produced through this method, such as polylactide (PLA)/natural rubber (NR), 13,14 PLA/epoxidized natural rubber (ENR), [15][16][17] PLA/nitrile butadiene rubber (NBR), 18 poly(vinylidene fluoride) (PVDF)/acrylic rubber (ACM), 19 ethylene-propylene-diene monomer (EPDM)/polypropylene (PP), [20][21][22][23] PVDF/ENR, 24 polyamide 12 (PA12)/hydrogenated acrylonitrile butadiene rubber (HNBR), 25 and ethylene octene copolymer (EOC)/poly dimethyl siloxane (PDMS) rubber. 26 The properties of TPVs strongly depended on the final morphology, which were affected by many factors, such as the cross-linking degree of the rubber phase, composition, viscosity and elasticity of individual components, preparation method, and processing condition.…”
Section: Introductionmentioning
confidence: 99%
“…The effective way to prepare TPVs is through dynamical vulcanization, which is the process of cross‐linking an elastomer during its melt mixing with a molten plastic under dynamic condition . A significant number of TPVs are produced through this method, such as polylactide (PLA)/natural rubber (NR), PLA/epoxidized natural rubber (ENR), PLA/nitrile butadiene rubber (NBR), poly(vinylidene fluoride) (PVDF)/acrylic rubber (ACM), ethylene‐propylene‐diene monomer (EPDM)/polypropylene (PP), PVDF/ENR, polyamide 12 (PA12)/hydrogenated acrylonitrile butadiene rubber (HNBR), and ethylene octene copolymer (EOC)/poly dimethyl siloxane (PDMS) rubber …”
Section: Introductionmentioning
confidence: 99%